Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\sqrt{3x^2-1}+\sqrt{x^2-x}-x\sqrt{x^2+1}=\frac{1}{2\sqrt{2}}\left(7x^2-x+4\right)\)
\(\Leftrightarrow2\sqrt{2}\left(\sqrt{3x^2-1}+\sqrt{x^2-x}-x\sqrt{x^2+1}\right)=7x^2-x+4\)
\(\Leftrightarrow\left[\left(3x^2-1\right)-2\sqrt{2}\sqrt{3x^2-1}+2\right]+\left[\left(x^2-x\right)-2\sqrt{2}\sqrt{x^2-x}+2\right]+\left[2x^2+2\sqrt{2}x\sqrt{x^2+1}+\left(x^2+1\right)\right]=0\)
\(\Leftrightarrow\left(\sqrt{3x^2-1}-\sqrt{2}\right)^2+\left(\sqrt{x^2-x}-\sqrt{2}\right)^2+\left(\sqrt{x^2+1}+\sqrt{2}x\right)^2=0\)
Làm nốt
ĐKXĐ: \(-1\le x\le\frac{5}{3}\)
\(\Leftrightarrow6-2x+2\sqrt{-3x^2+2x+5}=3x^2-4x+4\)
\(\Leftrightarrow-3x^2+2x+5+2\sqrt{-3x^2+2x+5}-3=0\)
Đặt \(\sqrt{-3x^2+2x+5}=t\ge0\)
\(\Rightarrow t^2+2t-3=0\Rightarrow\left[{}\begin{matrix}t=1\\t=-3\left(l\right)\end{matrix}\right.\)
\(\Rightarrow\sqrt{-3x^2+2x+5}=1\)
\(\Leftrightarrow-3x^2+2x+4=0\)
\(\Leftrightarrow...\)
\(P=\frac{3x+3\sqrt{x}-3-\left(\sqrt{x}+1\right)\left(\sqrt{x}-1\right)-\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}{x+\sqrt{x}-2}\)
\(P=\frac{3x+3\sqrt{x}-3-x+1-x+4}{x+\sqrt{x}-2}\)
\(P=\frac{x+3\sqrt{x}+2}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+2\right)}\)
\(P=\frac{\left(\sqrt{x}+1\right)\left(\sqrt{x}+2\right)}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+2\right)}=\frac{\sqrt{x}+1}{\sqrt{x}-1}\)
\(\sqrt{x^2+x+2}=\frac{3x^2+3x+2}{3x+1}\)
Đk:.... tự xác định :v
\(\Leftrightarrow\sqrt{x^2+x+2}-2=\frac{3x^2+3x+2}{3x+1}-2\)
\(\Leftrightarrow\frac{x^2+x+2-4}{\sqrt{x^2+x+2}+2}=\frac{3x^2-3x}{3x+1}\)
\(\Leftrightarrow\frac{\left(x-1\right)\left(x+2\right)}{\sqrt{x^2+x+2}+2}-\frac{3x\left(x-1\right)}{3x+1}=0\)
\(\Leftrightarrow\left(x-1\right)\left(\frac{x+2}{\sqrt{x^2+x+2}+2}-\frac{3x}{3x+1}\right)=0\)
Dễ thấy: \(\frac{x+2}{\sqrt{x^2+x+2}+2}-\frac{3x}{3x+1}< 0\)
\(\Rightarrow x-1=0\Rightarrow x=1\)
ĐKXĐ là x\(\ge\frac{2}{3}\)
\(\frac{x^2}{\sqrt{3x-2}}-\frac{3x-2}{\sqrt{3x-2}}=1-x\)
<=>x^2-3x+2=(1-x)\(\sqrt{3x-2}\)